High Level of Private Activity in Energy, Transport, and Water in IDA Countries in 2010 - Perard, Edouard (World Bank, Washington, DC, 2012)
In 2010, 24 energy, transport, and water projects with private participation reached financial or contractual closure in 12 of the 63 International Development Association (IDA) countries involving investment commitments of US$7.5 billion That investment represents a record level compared with the US$1 to US$3 billion annual investment's range of the last five years (US$1 billion in 2009). The number of projects also increased significantly with nine additional projects compared to 2009. This increase was driven mostly by the energy sector, which accounted for 19 of the 24 new projects and for US$6.8 billion in investments. In comparison the energy sector had only 10 projects in 2009 representing US$605 million in investments. The largest 2010 energy project was the Hongsa partially captive coal power plant in Laos, which involved investment commitments of US$3.7 billion. In addition to energy projects, four transport projects with private participation reached financial closure in four IDA countries representing more than US$728 million in investments.